CHEMICAL RENAL DENERVATION WITH ALCOHOL – LONG TERM RESULTS FROM THE PEREGRINE POST-MARKET STUDY. (June 2018) - Persu, A.; Renkin, J.; Hochul, M.; Wojakowski, W.; Böhm, M.; Mahfoud, F.; Schmieder, R.; van der Giet, M.; de Bucourt, M.; Zirlik, A.; Neuzil, P.; Haratani, N.; et al.
Abstract: Objective: The Peregrine post-market study is a prospective, single arm, open label, multicenter European trial evaluating the safety and performance of the Peregrine System™ Infusion Catheter (Ablative Solutions, Inc., Palo Alto, CA, USA) to perform chemical (alcohol) renal denervation (cRDN) to treat resistant hypertension (rHTN). Design and method: The trial allows treatment of up to 60 patients at up to 10 centers in Europe. Eligible patients have rHTN. Patients with white coat rHTN are excluded. After confirmation of anatomical eligibility, patients undergo bilateral cRDN with 0.6 mL of alcohol per renal artery using the Peregrine catheter. Major safety endpoints are assessed at 1 month. The major efficacy endpoint is the reduction of 24-hour mean (SABP) at 6 months, compared to baseline. It is anticipated that the at least 35 patients with BP data from 1 through 12 months will be presented. Results: Treated patients (61% of males) had a mean age of 55 yo, mean BMI of 32 ± 6 kg/m2 and mean eGFR of 85 ± 18 ml/min/1, 73m2. At baseline, mean Systolic Office blood pressure (SOBP) and mean SABP were 173 ± 16 mmHg and 153 ± 14 mmHg respectively (n = 31). All procedures were technically successful, with a mean procedure time of 7 ± 3 minutes/artery (n = 65). Two minor renal artery dissections that resolved without intervention and three (9%) vascular access site complications without sequelae were reported. There were no deaths, myocardial infarctions, strokes, transient ischemic attacks or renal events. At 1-month, mean SOBP and SABP reductions were −24 ± 22 mmHg (n = 28; p < 0.001) and −11 ± 13 mmHg (n = 26; p < 0.001), respectively. At 6-months, mean SOBP and SABP reductions were −18 ± 25 mmHg (n = 21; p = 0.002) and −14 ± 16 mmHg (n = 21; p = 0.005), respectively. In 2 of 28 patients (7%) anti-hypertensive medications were reduced at 1 month and in 3 of 24 patients (12%) at 3 months. In a single patient, antihypertensive medications were increased at 6 months. This abstract serves as a promissory for updated data to be presented. Conclusions: Chemical RDN using the Peregrine catheter is feasible, safe and accompanied by a significant BP reduction. Additional data from larger randomized, double-blind, clinical trials will be needed to confirm these results.